Is high levels of vitamin D a new risk factor for Peyronie's disease?. (10th July 2019) - Canat, Halil Lutfi; Can, Osman; Ozbir, Sait; Cakir, Suleyman Sami; Culha, Mehmet Gokhan; Bayraktarli, Recep Yilmaz; Atalay, Hasan Anıl
Abstract: The aim of this study is to investigate whether serum vitamin D level predicts the risk of Peyronie's disease. Calcium and inflammatory cytokines play an important role during fibrocalcification of the plaques in Peyronie's Disease. TGF‐β1 is one of the most fibrogenic cytokines. Increasing serum vitamin D levels is considered that induce expression of TGF‐β1. Serum vitamin D levels and TGF‐β1 are related with calcifications of some soft tissues in previous studies. One hundred and three Peyronie patients and 162 healthy volunteers were included in the study. In both groups, demographic data, medical history, physical examination and erectile capacity were recorded. Serum 25‐hydroxyvitamin D, total cholesterol, low‐density lipoprotein, high‐density lipoprotein, triglyceride and testosterone levels were measured. The mean level of serum 25 (OH) D was significantly higher in men with Peyronie's disease compared with the controls (32.6 ± 7.9 ng/ml vs. 18.5 ± 6.6 ng/ml respectively. p  < 0.001). There is a relationship between Peyronie's disease and high serum vitamin D levels. Also, increased low‐density lipoprotein and total cholesterol levels, diabetes mellitus, and cardiovascular diseases were associated with Peyronie's disease.